Global‐Scale Consistency of Spaceborne Vegetation Indices, Chlorophyll Fluorescence, and Photosynthesis. Issue 6 (25th June 2021) - Doughty, Russell; Xiao, Xiangming; Köhler, Philipp; Frankenberg, Christian; Qin, Yuanwei; Wu, Xiaocui; Ma, Shuang; Moore, Berrien
Abstract: The new TROPOspheric Monitoring Instrument (TROPOMI) solar‐induced chlorophyll fluorescence (SIF) data provides new opportunities to corroborate and improve global photosynthesis estimates. Here we report the spatiotemporal consistency between TROPOMI SIF and vegetation indices from the bidirectional reflectance distribution function (BRDF) adjusted (MCD43) and standard MODIS (MOD09) surface reflectance products, estimates of absorbed photosynthetically active radiation by chlorophyll (APARchl ) derived from National Centers for Environmental Prediction Reanalysis‐2 (NCEP2), MODIS MCD18, and European Reanalysis (ERA5) data, and two GPP products (GPPVPM and GPPMOD17 ). We find (a) non‐adjusted VIs were more highly correlated with SIF at mid and high latitude than BRDF‐adjusted VIs, but were less correlated in the tropics, (b) negligible differences in the correlation between SIF and non‐adjusted NIRv and EVI, but BRDF‐adjusted NIRv had higher correlations with SIF at mid to high latitude than BRDF‐adjusted EVI but lower correlations in the tropics, (c) choice of PAR data set likely to cause substantial differences in global and regional GPP estimates and the correlation between modeled GPP and SIF, (d) SIF was more highly correlated with APARchl at high to mid latitude than EVI but more highly correlated with EVI at lower latitudes, and (e) GPPVPM is more highly correlated with SIF than GPPMOD17, except in sub‐Sahara Africa. Our results highlight that spaceborne photosynthesis would likely be improved by using a non‐linear response to PAR and that the fundamental differences between the vegetation indices and PAR data sets are likely to yield important differences in global and regional estimates of photosynthesis. Plain Language Summary: The validation of global, satellite‐based estimates of terrestrial photosynthesis has traditionally been conducted using a network consisting of a couple of hundred observation towers. However, these towers are not uniformly distributed across Earth's biomes and are largely concentrated in North America, Europe, and East Asia. Recent advancements in the detection of solar‐induced chlorophyll fluorescence (SIF), which is emitted from plants during photosynthesis, from space now affords us an opportunity to further validate satellite‐based photosynthesis and investigate how such estimates may be improved. The recently launched TROPOspheric Monitoring Instrument (TROPOMI) provides daily global scans at a relatively high spatial resolution. Here, we compare at the global‐scale TROPOMI SIF to satellite‐based photosynthesis, vegetation indices, and estimates of the amount of sunlight absorbed by chlorophyll (APARchl ), the latter two of which are used for estimating photosynthesis. Although we found TROPOMI SIF to be consistent with satellite‐based photosynthesis, vegetation indices, and APARchl, we found that SIF was better correlated with APARchl at high to mid latitude and better correlated with EVI at lower latitudes. This discrepancy indicates that modeling GPP as a non‐linear response to PAR would improve spaceborne estimates of photosynthesis. Key Points: Latitudinal differences in correlation between TROPOspheric Monitoring Instrument chlorophyll fluorescence and non‐adjusted and bidirectional‐adjusted vegetation indices Choice of solar radiance data product likely to yield substantial regional differences in estimates of the amount of sunlight absorbed by chlorophyll Modeling gross primary production as a non‐linear response to photosynthetically active radiation would likely improve satellite‐based estimates of gross primary production